Світовий асортимент культиварів квітниково-декоративних рослин родини ранникових (Scrophulariaceae Juss.) та перспективи їх інтродукції в Україну - Мuzychuk, G.М.; Prokopchuk, V.М. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
In result of the Figwort family's (Scrophulariaceae Juss.) plants world assortment study the list of species that are draw in selection process is worked out and the number of sort are determined for everyone. It have been fixed, that 1,0 thousand kinds (without Antirrhinum majus L. this number is 734) for 119 the family's species are selected. Ten the most perspective plants for their cultivars introduction were picked out. The propositions of Scrophulariaceae family sorts using for Ukrainian assortment decorative plants' quantity and quality structure improvement were worked out.